Case report: Phenotype expansion and analysis of TRIO and CNKSR2 variations - Liu, Yuefang; Liang, Zhe; Cai, Weili; Shao, Qixiang; Pan, Qiong (Frontiers in Neurology, 2022)
Introduction: TRIO and CNKSR2 have been demonstrated as the important regulators of RAC1. TRIO is a guanine exchange factor (GEF) and promotes RAC1 activity by accelerating the GDP to GTP exchange. CNKSR2 is a scaffold and adaptor protein and helps to maintain Rac1 GTP/GDP levels at a concentration conducive for dendritic spines formation. Dysregulated RAC1 activity causes synaptic function defects leading to neurodevelopmental disorders (NDDs), which manifest as intellectual disability, learning difficulties, and language disorders. Case presentation: Here, we reported two cases with TRIO variation from one family and three cases with CNKSR2 variation from another family. The family with TRIO variation carries a novel heterozygous frameshift variant c.3506delG (p. Gly1169AlafsTer11), where a prenatal case and an apparently asymptomatic carrier mother with only enlarged left lateral ventricles were firstly reported. On the other hand, the CNKSR2 family carries a novel hemizygous nonsense variant c.1282C>T (p. Arg428*). Concurrently, we identified a novel phenotype never reported in known pathogenic CNKSR2 variants, that hydrocephalus and widening lateral ventricle in a 6-year-old male of this family. Furthermore, the genotype-phenotype relationship for TRIO, CNKSR2 and RAC1 were explored through a literature review. Conclusions: The novel variants and unique clinical features of these two pedigrees will help expand our understanding of the genetic and phenotypic profile of TRIO- and CNKSR2-related diseases.